Relationship of amplified dihydrofolate reductase genes to double minute chromosomes in unstably resistant mouse fibroblast cell lines. - Brown, P C (1981)
Murine 3T6 selected in increasing concentrations of methotrexate were unstable with respect to dihydrofolate reductase overproduction and methotrexate resistance when they are cultured in the absence of methotrexate. An analysis of the karyotypes of these resistant cells revealed the presence of numerous double minute chromosomes. We observed essentially identical kinetics of loss of dihydrofolate reductase gene sequences in total deoxyribonucleic acid and in deoxyribonucleic acid from fractions enriched in double minute chromosomes and in the numbers of double minute chromosomes per cell during reversion to methotrexate sensitivity, and this suggested that unstably amplified gene sequences were localized on double minute chromosomes. This conclusion ws also supported by an analysis of cell populations sorted according to dihydrofolate reductase enzyme contents, in which relative gene amplification and double minute chromosome content were related proportionally.